Chaparral bird community responses to prescribed fire and shrub removal in three management seasons. Issue 4 (13th February 2018) - Newman, Erica A.; Potts, Jennifer B.; Tingley, Morgan W.; Vaughn, Charles; Stephens, Scott L.
Abstract: Chaparral, a type of shrubland common throughout the California Floristic Province, is subject to management and removal in regions where wildfire threatens human lives and property. Management practices include conducting prescribed burns outside of the historical fire season and employing mechanical fuel reduction (mastication). As the wildland–urban interface grows, particularly in coastal California, more of this ecosystem is subject to active management. To understand the ecological implications of current California chaparral fire management practices, we studied bird species composition, abundance and foraging guilds in managed and unmanaged chaparral over 5 years. Study areas were located in Mendocino County in the coast ranges of northern California. We contrast six chaparral removal or "fuels manipulation" treatments: (1) fall fire, (2) winter fire, (3) spring fire, (4) fall mastication, (5) spring mastication and (6) untreated control. Treatments and controls were implemented in plots 2 ha or larger, and replicated four times each. We find that species richness in prescribed fire treatments reaches comparable levels to controls in the first 3 years following treatment, whereas masticated units always have lower species richness. Generalized linear mixed models additionally confirm that mastication has highly negative effects on observed abundances of birds compared to controls and to prescribed fire. The season in which fuels reduction occurred was less important to species richness, although fall fire was more beneficial to bird abundance than spring or winter fire. Fire treatments in all seasons maintain the same general bird community structure as controls, while mastication results in strongly differentiated assemblages, increasing granivores while nearly excluding foliage gleaners. Synthesis and applications . We compare two California chaparral management techniques, prescribed fire and mastication, in three seasons (fall, winter and spring) in northern California, USA. We tracked chaparral bird community response in 23 experimental units for 2–5 years. We conclude that prescribed fire and mastication are not interchangeable management techniques, and that mastication negatively impacts bird communities, altering guild structure and reducing both diversity and abundance. Abstract : We compare two California chaparral management techniques, prescribed fire and mastication, in three seasons (fall, winter and spring) in northern California, USA. We tracked chaparral bird community response in 23 experimental units for 2–5 years. We conclude that prescribed fire and mastication are not interchangeable management techniques, and that mastication negatively impacts bird communities, altering guild structure and reducing both diversity and abundance.